Early mathematics learning : Selected Papers of the POEM 2012 Conference - Brandt, Birgit; Benz, Christiane; Krummheuer, Gotz; Ladel, Silke; Vogel, Rose; Kortenkamp, Ulrich (Springer New York, 2014)
This book will gather current research in early childhood mathematics education. A special focus will be the tension between instruction and construction of knowledge. The book includes research on the design of learning opportunities, the development of mathematical thinking, the impact of the social setting and the professionalization of nursery teachers.